Mieszkańcy miasta Elbląga! w dniu 22 lipca 1951 r. odbędę się zabawy ludowe. (Elbląg : [s.n.], 1951)
Afisz z programem uroczystości.
Keywords: Elbląg (Polska) -- 1945-1970 -- druki ulotne; Elbląg (Polska) -- 1945-1970 -- źródła